2009
DOI: 10.1097/jdn.0b013e3181a822d0
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Protection Behaviors and Beliefs Among Young Adult Dermatology Patients

Abstract: Background: Although skin cancer is the most common form of cancer in the United States, it is highly preventable by reducing exposure to ultraviolet radiation. This descriptive, correlational study describes the ultraviolet protection behaviors and beliefs of young adult dermatology patients. Methods: Eighty-two dermatology patients aged 18Y30 years were recruited from a suburban dermatology clinic in northern Utah. An investigator-developed questionnaire assessed ultraviolet protection stages of change, atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It is important to consider why indoor tanning bed users scored higher on the questionnaire than non-tanning bed users. Previous research is not conclusive about whether or increasing a person's knowledge correlates with behavioral change (Linton, 2009, Gibson, 2005Green, 2003. Previous studies also reported that individuals who were considered at high-risk for skin cancer or who already been diagnosed with skin cancer were significantly more likely to be counseled by a healthcare provider about skin cancer prevention (Freiman, 2005).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider why indoor tanning bed users scored higher on the questionnaire than non-tanning bed users. Previous research is not conclusive about whether or increasing a person's knowledge correlates with behavioral change (Linton, 2009, Gibson, 2005Green, 2003. Previous studies also reported that individuals who were considered at high-risk for skin cancer or who already been diagnosed with skin cancer were significantly more likely to be counseled by a healthcare provider about skin cancer prevention (Freiman, 2005).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…One study specifically examined dermatology patients' knowledge and reported that dermatology patients perceived sun protective measures as positive. Ironically, dermatology patients demonstrated inadequate use of protective measures (Linton, 2009).…”
Section: Ultraviolet Radiation Exposure Knowledge and Perceptionsmentioning
confidence: 99%
“…None of the respondents mentioned skin self-assessment as a preventive measure against skin cancer. In a study of young adult beliefs about ultraviolet (UV) protection behaviors, Linton and Jones (2009) found that the UV protection beliefs within the sample population were generally favorable and that the participants had adequate knowledge of the risks of UV exposure.…”
Section: Beliefs and Attitudesmentioning
confidence: 99%
“…One study specifically examined dermatology patients' knowledge and reported that dermatology patients perceived sun protective measures as positive. Ironically, dermatology patients demonstrated inadequate use of protective measures (Linton, 2009). Cottrell ( 2005) also found that although college age students could correctly identify sun protective measures, their use of sunscreen and other UV protective behaviors were low.…”
Section: Ultraviolet Radiation Exposure Knowledge and Perceptionsmentioning
confidence: 99%